Issues in the Philosophy of Logic: An Unorthodox Approach - Guillermo E. Rosado Haddock (Principia: An International Journal of Epistemology, 2007)
In this paper six of the most important issues in the philosophy of logic are examined from a standpoint that rejects the First Commandment of empiricist analytic philosophy, namely, Ockham’s razor. Such a standpoint opens the door to the clarification of such fundamental issues and to possible new solutions to each of them.